Longing in the Song Ummi by Maher Zain and Jasa Poma by Rafly Kande (A Comparative Literature Study) - Raihan Fitri; Fahmi Sofyan; Aiyub Berdan; Nur Chalis (Jurnal Bastra (Bahasa dan Sastra), 2026)
This study aims to reveal the similarities and differences in the theme of longing in Ummi by Maher Zain and Jasa Poma by Rafly Kande. The study is motivated by the discovery of these two songs, which share a similar meaning of “mother” expressed in two different languages. The research method applied in this study is a qualitative method. The data collection strategy uses the reading and note-taking technique. The data were analyzed using descriptive and comparative techniques to draw conclusions. The results of the study indicate that both songs share similarities in the elements of longing, particularly the longing for a mother’s love, a mother’s prayers, and devotion to the mother. Meanwhile, the differences lie in the cultural backgrounds: Jasa Poma is rooted in Acehnese culture, while Ummi is based on Middle Eastern culture. Furthermore, Jasa Poma belongs to the genre of Acehnese socio-religious poetry, while Ummi represents contemporary music, which influences the message delivered in both songs. The study also finds the portrayal of the mother figure in Ummi. Both Ummi and Jasa Poma possess unique characteristics as original literary works.